PENILAIANKINERJA KOPERASI PEGAWAI REPUBLIK INDONESIA (KPRI) â€SRI REJEKIâ€ KECAMATAN DONOMULYO BERDASARKAN PERATURAN MENTERI NEGARA KOPERASI DAN USAHA KECIL DAN MENENGAH NO.14/PER/M.UMKM/XII/2009 - Wiseptya, Agris; Indrawati, Nur Khusniyah (Jurnal Ilmiah Mahasiswa FEB, 2014)
The existence of cooperative useful as a pillar of the national economy, according lofty goals listed in Pancasila and the 1945 Constitution is to realize prosperity for all Indonesian people.This study aims to analyze the health of financial and non-financial in Employees Cooperative Republic of Indonesia "Sri Rejeki" in Donomulyo District for five years (2009-2013). The study design was descriptive and the analysis methods based on the State Ministry of Cooperatives and SMEs Regulation No.14/Per/M.KUKM/XII/2009. The results showed that the predicate cooperative Sri Rejeki in Donomulyo District is quite healthy from 2009 to 2013 with score 69,2; 79,3; 71,8; 72,4; 72,4. Performance assessment indicated that the cooperative has increased performance. Some things to note in this cooperative is the SHU policies and utilization of idle cash. Currently, the cooperative has business activities, family atmosphere and excellent services provide to members. Key words : Performance, KPRI Sri Rejeki Donomulyo, State Ministry of Cooperative and SMEs, State Ministry of Cooperative and SMEs Regulation No.14/Per/M.UMKM/XII/2009.